Performance of Crohn's disease Clinical Trial Endpoints based upon Different Cutoffs for Patient Reported Outcomes or Endoscopic Activity: Analysis of EXTEND Data. Issue 5 (14th April 2018) - Feagan, Brian; Sandborn, William J; Rutgeerts, Paul; Levesque, Barrett G; Khanna, Reena; Huang, Bidan; Zhou, Qian; Maa, Jen-fue; Wallace, Kori; Lacerda, Ana; Thakkar, Roopal B; Robinson, Anne M
Abstract: Background: Clinical trial endpoints for Crohn's disease (CD) activity correlate poorly with mucosal inflammation; to assess treatment efficacy, patient-reported outcomes and endoscopic assessments are preferred. This study assessed the impact on treatment efficacy estimations of using different definitions of clinical and endoscopic remission and endoscopic response, and of using site- or central-based endoscopy evaluation. Methods: This post hoc analysis of data fromEXTEND (extend the safety and efficacy of adalimumab through endoscopic healing), a placebo (PBO)-controlled, randomized trial of adalimumab (ADA) for mucosal healing, included adults with moderate-to-severe CD. Subsets of patients meeting specified Simplified Endoscopic Score for CD (SES-CD) inclusion criteria, according to site or central reading, and baseline stool frequency (SF) and/or abdominal pain score (AP) thresholds were evaluated. Various endpoint definitions based on the Crohn's Disease Activity Index (CDAI), its SF and AP components, SES-CD, and composite endpoints were compared between treatment groups. Results: Increased stringency of Week 12 clinical endpoints compared to CDAI<150 to SF≤3.0/1.5&AP≤1.0 reduced PBO response rates by ≥12% and increased treatment effects by ≤10%. Amending the SES-CD endpoint from ≤4 to ≤2 reduced the treatment effect from 24% to 8%. Composite endpoints further diminished response rates and effect sizes. Site-based evaluation was associated with lower remission rates versus central reading in the PBO group and, thus, greater ADA-related treatment effects. Conclusions: This analysis is the first to demonstrate that increasing the stringency of clinical and endoscopic endpoint definitions in CD trials, especially lowering SF or SES-CD definitions, reduces the ability to detect treatment-related change in CD activity; focus on endpoints that reflect clinical change is warranted.